2016
DOI: 10.1073/pnas.1514005113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complex formed by β-glucocerebrosidase and the lysosomal integral membrane protein type-2

Abstract: The lysosomal integral membrane protein type-2 (LIMP-2) plays a pivotal role in the delivery of β-glucocerebrosidase (GC) to lysosomes. Mutations in GC result in Gaucher's disease (GD) and are the major genetic risk factor for the development of Parkinson's disease (PD). Variants in the LIMP-2 gene cause action myoclonus-renal failure syndrome and also have been linked to PD. Given the importance of GC and LIMP-2 in disease pathogenesis, we studied their interaction sites in more detail. Our previous data demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 34 publications
0
57
0
Order By: Relevance
“…[26][27][28][29][30] Furthermore, the use of peptides targeting helix 5 of LIMP-2 has been able to reduce α-syn levels by activating endogenous wild-type and mutant GCase. 31 These findings open a window for the design of small molecules targeting this domain to enhance LIMP-2/GCase interaction.…”
Section: Disruptions In Protein Traffickingmentioning
confidence: 94%
See 1 more Smart Citation
“…[26][27][28][29][30] Furthermore, the use of peptides targeting helix 5 of LIMP-2 has been able to reduce α-syn levels by activating endogenous wild-type and mutant GCase. 31 These findings open a window for the design of small molecules targeting this domain to enhance LIMP-2/GCase interaction.…”
Section: Disruptions In Protein Traffickingmentioning
confidence: 94%
“…Small molecular chaperones such as ambroxol and isofagomine, which target misfolded GCase and increase GCase trafficking to lysosomes, reduce α‐syn burden, in both in vitro and in vivo disease models and may have utility as disease‐modifying agents . Furthermore, the use of peptides targeting helix 5 of LIMP‐2 has been able to reduce α‐syn levels by activating endogenous wild‐type and mutant GCase . These findings open a window for the design of small molecules targeting this domain to enhance LIMP‐2/GCase interaction.…”
Section: Mechanisms Underlying the Cross Talk Between Gcase And α‐Synmentioning
confidence: 99%
“…Following correct folding of newly formed GCase molecules in the ER, these bind to the membrane protein LIMP2 (lysosomal membrane protein 2) [72][73][74]. This binding is mediated by hydrophobic helical interfaces on both proteins [75]. Action myoclonus renal failure syndrome (AMRF) is a recessively inherited disease caused by mutations in LIMP2 [76].…”
Section: Gcase Protein and Life Cyclementioning
confidence: 99%
“…. Following translation of GCase at the ER, GCase is transported via the Golgi to lysosomes via the transporter protein LIMP2, undergoing several glycosylation modifications on the way . Analysis of the glycosylated forms of GCase in the cortex of control human brains suggested that lysosomal maturation of GCase was diminished in brains with higher amounts of α‐synuclein .…”
Section: Decreased Gcase Activity In Sporadic Pdmentioning
confidence: 99%